Ionic liquid treated leaves of Juglans regia as an adsorbent for the removal of methyl orange dye: experimental, computational, and statistical approach. Issue 6 (12th May 2023) - Shah, Shahid Shafi; Sharma, Taniya; Kumar, Dinesh; Sharma, Sapna; Bamezai, Rajinder K.
Abstract: The novel biosorbents prepared by surface modification from leaves of Juglans regia plant were exploited for removal of methyl orange dye from aqueous solution. The leaves in the form of dust and charcoal were separately impregnated with 1-butyl-3-methyl imidazolium bromide (I) to obtain adsorbents namely J. regia dust/charcoal impregnated with I (JRDI/JRCI) which were characterized using advanced analytical approaches. The impregnation of ionic liquid was confirmed by the appearance of new bands. Langmuir isotherm fitted well; the calculated adsorption capacity being 59.37 (JRDI) and 102.72 mg g −1 (JRCI). The kinetic study revealed that sorption obeyed the pseudo-first order model; the experimental adsorption capacity being 53.53 (JRDI) and 86.82 mg g −1 (JRCI) at selected conditions of pH 3, initial dye concentration 100 ppm, dosage of adsorbent 0.3 g and contact time 70 min. The mathematical models which predicted adsorption capacity as 51.5 (JRDI) and 82.1 mg g −1 (JRCI) were found at par with experimental values. Fukui condensed functions revealed that adsorbents had electron deficient electrophilic reaction sites while dye had electron-rich nucleophilic reaction sites. The structural properties and good adsorption capability of adsorbents indicate that they could be used as potential, eco-friendly adsorbents for the treatment of negatively charged dye pollutants. Graphical Abstract: UF0001 NOVELITY STATEMENT: The research work is the first study on the sorption of methyl orange dye from an aqueous solution using ionic liquid impregnated leaves of J. regia plant in powder and biochar form. Juglans regia leaves are eco-friendly and cheap precursors for selected adsorbents. Impregnation of ionic liquid which makes the adsorbent surface positively charged is responsible for enhancing the adsorption capacity for negatively charged methyl orange dye. To the best of our knowledge, the use of impregnated ionic liquid in the leaves of plants as an adsorbent for the efficient removal of dye is very sparse. This motivated us to fill the gap by choosing ionic liquid and demonstrating the enhanced adsorption capacity of dye.